Hubungan Tingkat Kecemasan dengan Tingkat Nyeri Post Operatif Sectio Caesarea Teknik Anestesi Spinal - Saputra, Yeli; Sumarni, Tri; Khasanah, Suci (Universitas Harapan Bangsa Purwokerto, 2023)
Surgical procedures will cause feelings of anxiety for the patient and will also have an impact on the patient's pain intensity after sectio caesarea. The aim of this study was to determine the relationship between anxiety levels and pain levels in postoperative sectio caesarea using spinal anesthesia. This research method is quantitative with a descriptive correlation type with a cross sectional design. The number of samples in this study were 33 respondents with a total sampling technique according to the inclusion and exclusion criteria. Data analysis was performed univariately with frequency distribution and bivariately using the Spearman correlation test. The results showed that the majority of postoperative sectio caesarea patients experienced moderate anxiety as many as 17 respondents (51.5%) and moderate pain levels as many as 23 respondents (69.7%). The results of the Spearman correlation test showed that there was a significant correlation between the scores of preoperative anxiety levels and the pain level of postoperative sectio caesarea spinal anesthesia technique with a p-value of 0.002 (p<0.05). This study concludes that there is a relationship between the level of anxiety and the level of pain in postoperative sectio caesarea using spinal anesthesia at RSUD dr. Zubir Mahmud, East Aceh Regency.